2014
DOI: 10.3176/arch.2014.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Corded Ware in the Areas North of the Gulf of Finland – An Update

Abstract: Research of the Corded Ware phenomenon in the areas north of the Gulf of Finland has been scanty during the last several decades, and consequently outdated views, distribution maps, and numbers of finds still prevail. This paper aims to update data on the distribution of Corded Ware in Finland and Karelia (Russia), and to discuss the results in the context of the old research tradition, and to highlight some aspects of the northern Corded Ware. The current data shows that there are ca 360 Corded Ware settlemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 5 publications
0
12
1
4
Order By: Relevance
“…Artefact distributions show that the core area of Corded Ware settlement was in southern and western Finland (Figure 1). In contrast to the evidence from other regions, Finnish Corded Ware was also associated with large numbers of settlement sites, which are often found in the locations of Early Neolithic ( c. 5200–3900 cal BC) hunter-gatherer settlements (Äyräpää 1923: 26–27; Edgren 1984: 75; Nordqvist & Häkälä 2014).…”
Section: Introductioncontrasting
confidence: 67%
“…Artefact distributions show that the core area of Corded Ware settlement was in southern and western Finland (Figure 1). In contrast to the evidence from other regions, Finnish Corded Ware was also associated with large numbers of settlement sites, which are often found in the locations of Early Neolithic ( c. 5200–3900 cal BC) hunter-gatherer settlements (Äyräpää 1923: 26–27; Edgren 1984: 75; Nordqvist & Häkälä 2014).…”
Section: Introductioncontrasting
confidence: 67%
“…Both the pottery and battle axes exhibit stylistic elements peculiar to Baltoscandia (Larsson, 2009: 139-152;Lindström, 2003). People in the areas surrounding the Gulf of Finland were obviously in close contact during this period (Carpelan, 2004(Carpelan, , 2006Kriiska, 2000Kriiska, , 2009Lang and Kriiska, 2007;Mökkönen, 2008Mökkönen, , 2011Nordqvist, 2016;Nordqvist and Häkälä, 2014). It has been suggested that the CWC first spread to East Sweden from Finland, rather than from Denmark or Poland, as was previously assumed (Larsson, 2008(Larsson, , 2009.…”
Section: Introductionmentioning
confidence: 84%
“…Animal husbandry does not necessarily involve cultivation, which explains the absence of indications of cultivation from our pollen data, and why it is not visible in our population size estimate either. Moreover, there is a lack of any archaeological evidence for cultivation by CW people (Nordqvist and Häkälä, 2014), although Siiriäinen (1980) argued that their lack of hunting-related tools could indicate a subsistence based on something other than hunting. The first, modest indication for cultivation in the pollen spd dates to Kiukainen Culture (mean approximately 1500 BC).…”
Section: Discussionmentioning
confidence: 99%